2012
DOI: 10.1371/journal.pone.0047717
|View full text |Cite
|
Sign up to set email alerts
|

Integration of SNP and mRNA Arrays with MicroRNA Profiling Reveals That MiR-370 Is Upregulated and Targets NF1 in Acute Myeloid Leukemia

Abstract: BackgroundDeregulated miRNA expression plays a crucial role in carcinogenesis. Recent studies show different mechanisms leading to miRNA deregulation in cancer; however, alterations affecting miRNAs by DNA copy number variations (CNV) remain poorly studied.ResultsOur integrative analysis including data from high resolution SNPs arrays, mRNA expression arrays, and miRNAs expression profiles in 16 myeloid cell lines highlights that CNV are alternative mechanisms to deregulate the expression of miRNAs in acute my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
1
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 28 publications
2
23
1
3
Order By: Relevance
“…Interestingly, miR-370 has been reported to be associated with lipid metabolism, coronary artery disease as well as cell proliferation of epithelial and neuronal cell types (Chang et al, 2012; Gao et al, 2012; Garcia-Orti et al, 2012; Iliopoulos et al, 2010; Liu et al, 2012; Wu et al, 2012). MiR-328 has been described to modulate the expression of mouse beta-amyloid precursor protein-converting enzyme 1(Boissonneault et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, miR-370 has been reported to be associated with lipid metabolism, coronary artery disease as well as cell proliferation of epithelial and neuronal cell types (Chang et al, 2012; Gao et al, 2012; Garcia-Orti et al, 2012; Iliopoulos et al, 2010; Liu et al, 2012; Wu et al, 2012). MiR-328 has been described to modulate the expression of mouse beta-amyloid precursor protein-converting enzyme 1(Boissonneault et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The upregulated miRNAs in our studies include miR-21, which targets PTEN in non-small cell lung cancer [54]; cluster miR-221/miR-222, which is activated in Schwann cell proliferation following sciatic nerve injury by targeting LASS2 [55] and accelerates proliferation during liver regeneration [56]; and miR-370, which is capable of reducing NF1 mRNA levels in acute myeloid leukemia [57] and is also overexpressed in prostate cancer [58]. Another miRNA with increased expression is miR-493, which is defined as a tumor suppressor in bladder cancer and is capable of downregulating FZD4 and RhoC protein expression [59].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, we do not have miRNA expression data from our CNVs as RNA was not available. However, a recent study by Garcia-Orti et al [34], demonstrated 10% of 259 studied miRNAs from regions of gain and loss detected in AML had significant change in expression concordant with the type of copy number change.…”
Section: Discussionmentioning
confidence: 99%